Peningkatan Network Lifetime Menggunakan Cluster Based Pada Wireless Sensor Network - muhammad hibrian wiwi; Wardi Wardi; Agussalim Agussalim (JITCE (Journal of Information Technology and Computer Engineering), 2020)
This series of research activities are in the form of a routing simulation using the LEACH protocol as a cluster-based mechanism method that can improve Network Lifetime in the Wireless Sensor Network protocol, using the Network Simulator 2 application device that describes data transmission, remaining nodes, and energy used. Determination of the performance and power consumption of the wireless sensor network by testing scenario one to scenario five due to the influence of the cluster to be applied, such as scenario 1 using 1 cluster (C1) consumes an average of the energy of 0.155 joules and the data sent or obtained is 72,848 bytes. Barriers or disruptions to the clusterhead affect the performance of LEACH, so there is a need for criteria or conditions to determine which nodes should be used as clusterhead.